Analisis Tayangan Indonesia Lawyers Club di TV One bagi Pemahaman Politik - Anisah Ulfi; Prayetno Prayetno (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2018)
The aim of this research is to find out the understanding of the political community after watching the Episode "2019 presidential election: Jokowi getting stronger?". Data collection is done by Interview, Observation, and Documentation. The interviewees in this study were ten people from Hamlet XIII in Sei Rotan Village. The research method used in this study is a qualitative descriptive method and tends to use analysis as well as to highlight the process and meaning. Technical data analysis used in the study is data collection, data reduction, data presentation (data display) and conclusion (verification). The results of this reaserch show that Indonesian Lawyers Club Impressions on TV One Episode "2019 presidential election: Jokowi getting stronger?". Can provide political understanding for the community. Where related 5 (Five) Indicators in the form of understanding of the State, Government, Power, Political Parties and General Elections. As well as the benefits obtained by the community in the form of insights about politics, as well as benefits that lead to positive things for the community.